Beyond its preferential niche: Brucella abortus RNA down-modulates the IFN-γ-induced MHC-I expression in epithelial and endothelial cells - Serafino, Agustina (2024)
Brucella abortus (Ba) is a pathogen that survives inside macrophages. Despite being itspreferential niche, Ba infects other cells, as shown by the multiple signs and symptomshumans present. This pathogen can evade our immune system. Ba displays a mechanismof down-modulating MHC-I on monocytes/macrophages in the presence of IFN-γ (whenTh1 response is triggered) without altering the total expression of MHC-I. The retainedMHC-I proteins are located within the Golgi Apparatus (GA). The RNA of Ba is one of thePAMPs that trigger this phenomenon. However, we acknowledged whether this event couldbe triggered in other cells relevant during Ba infection. Here, we demonstrate that Ba RNAreduced the surface expression of MHC-I induced by IFN-γ in the human bronchial epithelium(Calu-6), the human alveolar epithelium (A-549) and the endothelial microvasculature(HMEC) cell lines. In Calu-6 and HMEC cells, Ba RNA induces the retention of MHC-I in theGA. This phenomenon was not observed in A-549 cells. We then evaluated the effect of BaRNA on the secretion of IL-8, IL-6 and MCP-1, key cytokines in Ba infection. Contrary to ourexpectations, HMEC, Calu-6 and A-549 cells treated with Ba RNA had higher IL-8 and IL-6levels compared to untreated cells. In addition, we showed that Ba RNA down-modulatesthe MHC-I surface expression induced by IFN-γ on human monocytes/macrophages via thepathway of the Epidermal Growth Factor Receptor (EGFR). So, cells were stimulated withan EGFR ligand-blocking antibody (Cetuximab) and Ba RNA. Neutralization of the EGFR tosome extent reversed the down-modulation of MHC-I mediated by Ba RNA in HMEC and A-549 cells. In conclusion, this is the first study exploring a central immune evasion strategy,such as the downregulation of MHC-I surface expression, beyond monocytes and couldshed light on how it persists effectively within the host, enduring unseen and escaping CD8+T cell surveillance.